Digital Content Development Strategy To Increase Public And Donor Awareness Of The Tresna Werdha Budi Pertiwi Social Care Program - Azzahra, Shafa Tasya; Widiatmoko Soewardikoen, Didit; Azhar, Hanif; Rahman, Yanuar (Advances In Social Humanities Research, 2025)
A nursing home is a place that provides care and housing services for the elderly who need assistance in living their daily lives. Tresna Werdha Budi Pertiwi Social Home is one of the many nursing homes in Bandung. Supporting the welfare of the elderly, this Budi Pertiwi nursing home does not charge any fees from its residents, this allows them to face uncertain funding challenges because they are completely dependent on community donations. To increase public awareness of the importance of the existence of this nursing home and create a more comfortable atmosphere for the elderly, utilizing social media by presenting creative content that involves the elderly, such as video storytelling about their daily activities is a fairly effective problem solving. This orphanage seeks to build an emotional bond between the residents of the orphanage and the audience. Persuasive communication strategies are used to encourage more donors to contribute to meeting the needs of the elderly. This approach not only aims to attract the attention of the public, but also creates empathy and collective awareness of the importance of providing support to the elderly.